Characterization of oyster water-soluble protein-EGCG conjugate and its antioxidant effects on linolic acid in emulsion system. (February 2023) - Li, Yue; Liu, Xiaoyang; Yin, Fawen; Li, Deyang; Jiang, Pengfei; Song, Liang; Nakamura, Yoshimasa; Zhou, Dayong
Abstract: (−)-Epigallocatechin-3-gallate (EGCG) is frequently used as a good antioxidant in food systems. In contrast, its antioxidant capacity was limited in the oil-in-water emulsion system due to its high hydrophilicity. Therefore, food-derived proteins with higher hydrophobicity were utilized to bind with EGCG and form new molecules that could stay in the oil-water interface to improve the stability of such emulsions. This study combined water-soluble protein (OWPs) extracted from oysters with EGCG to form the OWPs-EGCG complex. When combined with EGCG, the molecular weight and particle diameter (nearly 180–240 nm) of OWPs slightly increased in a dose-dependent manner by increasing the proportion of EGCG. Moreover, several conformational changes to OWPs by EGCG addition were found, such as the alteration of secondary structures, the fluorescence quenching, and the involvement of binding groups. The OWPs-EGCG complex (1:0.025) exhibited the highest emulsifying activities, while the ratio of 1:0.2 had the highest foaming stability. Furthermore, the OWPs-EGCG complex showed nearly 90% free radical scavenging activities with an increasing ratio of EGCG. In the established temporary storage model of OWPs-EGCG conjugate/linolic acid emulsion system, the OWPs-EGCG complex exhibited enhanced antioxidant effects against the oxidation of OWPs and linolic acid. This study provided a theoretical basis for the potential applications of food-derived proteins/EGCG conjugates on antioxidant effects against lipid oxidation in the emulsifying system.